Regional Economic Outlook, April 2012, Western Hemisphere. (Regional Economic Outlook, 2012)
Growth in much of Latin America remains solid, although it slowed during the second half of 2011 as result of the combined effects of policy tightening and global uncertainties. Under our baseline, we expect growth in Latin America and the Caribbean to moderate to about 3 3/4 percent in 2012, from about 4 1\2 last year. For many countries, high commodity prices and easy external financing conditions will provide tailwinds. For others, weak growth in the United States and other advanced-country partners, or homegrown fiscal problems, will hold back activity. This edition of the Regional Economic Outlook: Western Hemisphere elaborates on three key themes. First, the global economic environment is somewhat better than in late 2011, but remains risky as renewed tensions from Europe and the likelihood of an oil price shock cannot be discarded. Second, external conditions will remain stimulative for much of Latin America: The double tailwinds of easy external finance and high commodity prices are likely to persist for a while, though not forever. And third, this environment creates opportunities for Latin America-opportunities to build on the resilience and flexibility that has served it so well during the global crisis of 2008-09. This edition also expands on these themes through analytical features on regional spillovers, the growth effects of global financial shocks, and housing and mortgage markets in the region.